2013
DOI: 10.1038/modpathol.2012.132
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of neural stem and progenitor cell markers nestin and SOX2 in distinguishing nodal melanocytic nevi from metastatic melanomas

Abstract: Sentinel lymph node evaluation is a critical component of melanoma staging, and lymph node status provides one of the most powerful predictors of melanoma recurrence and survival. One of the well-known diagnostic pitfalls in melanoma sentinel lymph node evaluation is the presence of nodal melanocytic nevi, which has been demonstrated in up to 26% of lymphadenectomy specimens and specifically in melanoma patients. Melanocytic markers enhance the sensitivity of melanoma detection in sentinel lymph nodes. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 25 publications
1
30
1
4
Order By: Relevance
“…Recent studies have highlighted the significance of SOX2 in melanoma progression. In particular, research has found SOX2 to influence melanoma cell invasion (Girouard et al., ) and to be coexpressed with nestin in patient samples (Chen et al., ; Laga et al., ). Moreover, SOX2 expression in melanoma patient samples was found to correlate with increased tumor thickness (Laga et al., ), which suggests a potential role for SOX2 in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have highlighted the significance of SOX2 in melanoma progression. In particular, research has found SOX2 to influence melanoma cell invasion (Girouard et al., ) and to be coexpressed with nestin in patient samples (Chen et al., ; Laga et al., ). Moreover, SOX2 expression in melanoma patient samples was found to correlate with increased tumor thickness (Laga et al., ), which suggests a potential role for SOX2 in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…The staining was strongest in the basal cell layer and progressively decreased with maturing epithelium. Although SOX2 is not considered to 40 Our findings indicate that unlike its potential role as a cancer stem-like cell/ tumor-initiating cell marker in various cancers such as lung adenocarcinoma, 41 gastric carcinoma, 42 breast carcinoma, 43 head and neck squamous cell carcinomas, 44 and metastatic melanomas, 45 it does not appear to mediate regulation of progenitor cells of the folliculo-sebaceous unit or interfollicular epidermis from which basal cell carcinomas originate. 29 The differential expression of SOX2 not only allows for a reliable distinction between basal cell carcinomas and basaloid squamous cell carcinomas but also provides opportunities for selective therapeutic intervention in basaloid squamous cell carcinomas.…”
Section: Clinical Follow-upmentioning
confidence: 95%
“…Moreover, Chen et al [17] reported that nestin is expressed in vascular endothelial cells; thus, lymph node blood vessels served as internal positive controls. In our study, nestin expression was observable in endothelial cells in all melanoma cases.…”
Section: Immunohistochemistrymentioning
confidence: 99%